The Echo of the Prague Congress in Hungary in the Contemporary Press and Political Thought - Mészáros, Andor (Historical Studies on Central Europe, 2025)
At the turn of the eighteenth and nineteenth centuries, the Hungarian state faced a significant dilemma: It had to assert its independence within the Habsburg Empire while navigating the challenges of modern ethnic and linguistic national movements in Hungary. Many members of the reform-era Hungarian aristocracy believed that modernization, urbanization, and the extension of rights would lead to the assimilation or, at least, to loyalty of non-Hungarian groups. They envisioned a multi-ethnic state where Hungarian would be the official language for political and administrative purposes, while acknowledging the existence of other languages within the realm. This concept of a ‘Hungarian political nation’ was later formalized in the 1867 Compromise. However, others warned that the rise of Hungarian nationalism could alienate non-Hungarian groups, particularly the Slavs, and competing nation-building processes might be a threat to the integrity of the multi-ethnic Hungarian state. Intended to foster Slavic cooperation within the Habsburg Empire, the Prague Congress in June 1848 further intensified concerns. While initially seen as a potential ally against Austrian dominance, the Congress’s pronouncements on Slavic rights and autonomy were perceived as a threat to Hungarian statehood. Kossuth, in particular, reacted strongly to the Congress’s accusations of Hungarian oppression and its calls for Slavic independence. The Prague Congress had a profound impact on Hungarian political thought. It solidified the perception of Slavic nationalism as a threat to the integrity of the Hungarian Kingdom. Rather than fostering cooperation, the Congress turned out to be a symbol of conflict and a point of contention in Hungarian-Slavic relations.